2010
DOI: 10.1007/s12192-009-0159-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen induces a cytoprotective and angiogenic response in human microvascular endothelial cells

Abstract: A genome-wide microarray analysis of gene expression was carried out on human microvascular endothelial cells (HMEC-1) exposed to hyperbaric oxygen treatment (HBOT) under conditions that approximated clinical settings. Highly up-regulated genes included immediate early transcription factors (FOS, FOSB, and JUNB) and metallothioneins. Six molecular chaperones were also up-regulated immediately following HBOT, and all of these have been implicated in protein damage control. Pathway analysis programs identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 34 publications
6
91
0
5
Order By: Relevance
“…Hyperbaric oxygen treatment (HBOT) seems to have beneficial effects on wound healing and reparative angiogenesis [73]. Global gene expression analysis on human microvascular endothelial cells exposed to hyperbaric oxygen under conditions similar to a clinical treatment showed that some metallothioneins especially MT-1E, MT-1F, MT-1G, MT-1H, MT-1M and MT-1X were up-regulated immediately after HBOT, some metallothioneins as MT-1E, MT-1F, MT-1H and MT-1X after 24 h [73].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Hyperbaric oxygen treatment (HBOT) seems to have beneficial effects on wound healing and reparative angiogenesis [73]. Global gene expression analysis on human microvascular endothelial cells exposed to hyperbaric oxygen under conditions similar to a clinical treatment showed that some metallothioneins especially MT-1E, MT-1F, MT-1G, MT-1H, MT-1M and MT-1X were up-regulated immediately after HBOT, some metallothioneins as MT-1E, MT-1F, MT-1H and MT-1X after 24 h [73].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…We should note, however, that because most studies to date have been carried out in cell culture and at super-physiological concentrations, there remain high returns to research focusing on the magnitude of these benefits under more natural conditions. Another pathway associated with longevity extension that is activated by xenohormetic compounds involves transcription factor nuclear factor-E2-related factor 2 (Nrf2; Godman et al 2009;Onken and Driscoll 2010). Nrf2 binds antioxidant response elements upstream of cytoprotective stress response proteins such as heme oxygenase and Hsp 22/40/90.…”
Section: Xenohormetic Compounds and Longevity Pathwaysmentioning
confidence: 99%
“…(d) As shown in Fig. 2 [21]. Hence, in this study, a widely used endothelial cell line HUVECs was adopted to explore ROS origination.…”
Section: Discussionmentioning
confidence: 99%